2003
DOI: 10.1002/nau.10171
|View full text |Cite
|
Sign up to set email alerts
|

A review of non‐invasive electro neuromodulation as an intervention for non‐neurogenic bladder dysfunction in children

Abstract: There are clear benefits from the use of electroneuromodulation in children with differing forms of voiding dysfunction. The treatment approach is independent of cognitive and pharmacological therapy, is minimally invasive, and free of side effects. To date, there are no clinical variables that reliably predict efficacy of electrotherapy in the various presentations of over and under active detrusor, sphincter dyssynergia, or irritative symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…Embora mais que 1/3 das crianças portadoras de distúrbio miccional apresentem alguma forma de atividade inapropriada do assoalho pélvico, casos com dissinergia do assoalho pélvico não são relatados separadamente e as coortes apresentadas não são uniformes, têm amostragens pequenas e sem grupo-controle. Embora concordem quanto aos níveis de segurança e evidên-cias iniciais de eficácia, todos os autores sugerem estudos controlados para a demonstração indiscutível da utilidade das técnicas 19 . Considerando os argumentos éticos envolvidos, em todos estes estudos as técnicas de estimulação foram usadas em associação ao tratamento convencional (farmacológico), o que dificulta a avaliação isolada dos resultados das técnicas de eletroestimulação, mesmo considerando pacientes refratários ao tratamento farmacológico após mais de dois anos de uso.…”
Section: Discussionunclassified
“…Embora mais que 1/3 das crianças portadoras de distúrbio miccional apresentem alguma forma de atividade inapropriada do assoalho pélvico, casos com dissinergia do assoalho pélvico não são relatados separadamente e as coortes apresentadas não são uniformes, têm amostragens pequenas e sem grupo-controle. Embora concordem quanto aos níveis de segurança e evidên-cias iniciais de eficácia, todos os autores sugerem estudos controlados para a demonstração indiscutível da utilidade das técnicas 19 . Considerando os argumentos éticos envolvidos, em todos estes estudos as técnicas de estimulação foram usadas em associação ao tratamento convencional (farmacológico), o que dificulta a avaliação isolada dos resultados das técnicas de eletroestimulação, mesmo considerando pacientes refratários ao tratamento farmacológico após mais de dois anos de uso.…”
Section: Discussionunclassified
“…STC was diagnosed by nuclear colonic transit study as reported by a nuclear medicine physician. Previous studies of TESIC for STC in children have used nuclear transit studies to demonstrate initial diagnosis [18][19][20][21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly, transcutaneous electrical stimulation using interferential current (TESIC) is utilised for a variety of conditions, including musculoskeletal pain and urinary incontinence [19]. TESIC has shown promise in the treatment of STC in children and has been shown to produce diarrhea in patients who are being treated for bladder instability [20][21][22][23][24][25][26].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a useful noninvasive therapeutic option that is used as a conservative treatment with positive results in bladder overactivity (7).…”
Section: Introductionmentioning
confidence: 99%